Mechanical Performances of Isolated Cuticles Along Tomato Fruit Growth and Ripening - Benítez, José J.; Guzmán-Puyol, Susana; Vilaplana, Francisco; Heredia-Guerrero, José A.; Domínguez, Eva; Heredia, Antonio (Frontiers in Plant Science, 2021)
The cuticle is the most external layer that protects fruits from the environment and constitutes the first shield against physical impacts. The preservation of its mechanical integrity is essential to avoid the access to epidermal cell walls and to prevent mass loss and damage that affect the commercial quality of fruits. The rheology of the cuticle is also very important to respond to the size modification along fruit growth and to regulate the diffusion of molecules from and towards the atmosphere. The mechanical performance of cuticles is regulated by the amount and assembly of its components (mainly, cutin, polysaccharides and waxes). In tomato fruit cuticles, phenolics, a minor cuticle component, have been found to have a strong influence on their mechanical behavior. To fully characterize the biomechanics of tomato fruit cuticle, transient creep, uniaxial tests and multi strain dynamic mechanical analysis (DMA) measurements have been carried out. Two well-differentiated stages have been identified. At early stages of growth, characterized by a low phenolic content, the cuticle displays a soft elastic behavior. Upon increased phenolic accumulation during ripening, a progressive stiffening is observed. The increment of viscoelasticity in ripe fruit cuticles has also been associated with the presence of these compounds. The transition from the soft elastic to the more rigid viscoelastic regime can be explained by the cooperative association of phenolics with both the cutin and the polysaccharide fractions.